Histological Subtypes of Brain Tumor: Pattern in a Hospital in Dhaka, Bangladesh (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2013)
Background: A brain tumor is an intracranial solid neoplasm which involves varied types of cells. Management strategies and prognosis of tumor depends on the combination of factors like the type and grade of tumor, its location, size and state of development. So definite typing of brain tumor by histological examination is essential for appropriate treatment.Methods: This cross-sectional study was carried out from May 2011 to June 2012 in Delta Hospital Limited, Dhaka, Bangladesh. A total of 65 brain tissue biopsy samples were collected irrespective of age and sex along with patients clinical diagnoses, CT scan or MRI report, and operative findings and histological diagnosis were done. The frequency and proportion were calculated using SPSS 12.0 for Windows.Results: Majority (38.5%) of the study subjects belonged to 4049 years of age group with male predominance (63.1%). Astrocytoma comprised the largest group (27.7%) and majority of the tumors were in spinal region (23.1%).Conclusions: It is concluded from this study that among the different varieties of brain lesions astrocytoma is the most common one and the location of tumor is more common in spinal region with male predominance between the age group of 4049 years confirmed by biopsy and histopathology along with CT or MRI.DOI: http://dx.doi.org/10.11566/cmoshmcj.v12i1.20Chatt Maa Shi Hosp Med Coll J 2013; 12(1): 9-11